2003
DOI: 10.1038/nsb895
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of a phosphorylation-dependent activator by an HDAC–PP1 complex

Abstract: The second messenger cAMP stimulates transcription with burst-attenuation kinetics that mirror the PKA-dependent phosphorylation and subsequent protein phosphatase 1 (PP1)-mediated dephosphorylation of the cAMP responsive element binding protein (CREB) at Ser133. Phosphorylation of Ser133 promotes recruitment of the co-activator histone acetylase (HAT) paralogs CBP and P300, which in turn stimulate acetylation of promoter-bound histones during the burst phase. Remarkably, histone deacetylase (HDAC) inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
168
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(174 citation statements)
references
References 41 publications
5
168
1
Order By: Relevance
“…In fact, it is known that PP1 does not have good substrate specificity, and that the PP1-interacting proteins not only localize PP1 to different cellular compartments, but can also deliver PP1 to close proximity of potential substrates, increasing PP1 substrate specificity and catalytic efficiency (Hu et al, 2006). Consistently, it has been recently reported that HDAC1 interacts with PP1 and is critical for the efficient action of PP1 on CREB1 (Canettieri et al, 2003). These data and the interaction between PP1 and CCDC6, showed in our experiments, suggested a possible interaction also between HDAC1 and CCDC6 that we have analyzed and confirmed.…”
Section: Ccdc6 Represses Creb1 Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, it is known that PP1 does not have good substrate specificity, and that the PP1-interacting proteins not only localize PP1 to different cellular compartments, but can also deliver PP1 to close proximity of potential substrates, increasing PP1 substrate specificity and catalytic efficiency (Hu et al, 2006). Consistently, it has been recently reported that HDAC1 interacts with PP1 and is critical for the efficient action of PP1 on CREB1 (Canettieri et al, 2003). These data and the interaction between PP1 and CCDC6, showed in our experiments, suggested a possible interaction also between HDAC1 and CCDC6 that we have analyzed and confirmed.…”
Section: Ccdc6 Represses Creb1 Activitymentioning
confidence: 96%
“…Recently, it has been shown that PP1 can be targeted to CREB1, for efficient dephosphorylation, through binding of PP1 to HDAC1 (Canettieri et al, 2003) or HDAC8 proteins (Gao et al, 2009). HDACs catalyze the removal of acetyl groups from core histones (Marks et al, 2001), inducing local condensation of chromatin.…”
Section: Ccdc6 Physically Interacts With Hdac1mentioning
confidence: 99%
“…Reduced PP1 may have important effects for transcriptional regulation by CREB through the ability of PP1 to complex with HDAC. Canettieri et al (2003) demonstrated that a HDAC1-PP1 complex represses CREB activation under basal conditions and dephosphorylates CREB to return the system to baseline after a stimulus. This suggests that repression of PP1 is crucial in providing phosphorylated CREB with the capacity to recruit CBP to the promoter, at which time histones become acetylated and help to drive the transcription of particular genes.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal promoter region of follistatin, containing MyoD-, CREBand NFAT-responsive elements, regulates muscle-restricted expression of follistatin 8 . Selective association of MyoD and CREB with class I histone deacetylases (HDACs) represses downstream gene transcription 13,14 , and only the class I HDACs HDAC1 and HDAC2 occupied the chromatin of the proximal follistatin promoter in myoblasts (Fig. 2e).…”
mentioning
confidence: 99%